[Student in Yosemite dorm room] (1977)
A student sits in a Yosemite Hall dorm room with beauty and cleaning supplies on the window. A Bible sits against the far side, with two vacuums and a travel trunk. Apples are sitting in a bowl on a side table, as well as a small house plant.